Hamlet - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. No fear Shakespeare graphic novels., 2020)
When his father is murdered by his uncle, who is then named king, Prince Hamlet takes it upon himself to delve out justice while everyone around him believes that he is going mad.